The long-run effects of mortality decline in developing countries - Ulla Lehmijoki; Tapio Palokangas (Institute for the Study of Labor (IZA), 2011)
Since World War II, mortality has declined in the developing world. This paper examines the effects of this mortality decline on demographic and economic growth by a family-optimization model, in which fertility is endogenous and wealth yields utility through its status. The decline in mortality stimulates investment and generates an income stream which promotes population growth, but the desire of status hampers fertility and prevents capital-diluting demographic expansion. If status-seeking is strong, then the decline of mortality decreases population growth below its original level.
urn:nbn:de:101:1-201104084330
Keywords: O41; J13; J10; O10; 330; mortality; population growth; economic growth; Sterblichkeit; Bevölkerungswachstum; Wirtschaftswachstum; Familienökonomik; Sozialer Status; Fruchtbarkeit; Bevölkerungsökonomie; Entwicklungsländer